MODELOWANIE HAŁDY KRUSZYWA NATURALNEGO Z WYKORZYSTANIEM TECHNOLOGII UAV WRAZ Z ANALIZĄ DOKŁADNOŚCI - SMACZYŃSKI, MACIEJ (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2025)
The purpose of this article is to determine the potential of imaging obtained using an unmannedaerial platform (UAV) to create a digital model of terrain for aggregate heaps (DTMs). In addition, the intermediategoal is to carry out an independent accuracy check of the calculated 3D model, which in the study will be referred to an independent measurement using GNSS technology. The research object was a heap of natural aggregate with irregular shape and height differences up to 11 meters. Three point clouds with different detail parameters were generated from the acquired images. For further analysis, a point cloud with the best ratio of terrain reflection accuracy to the calculated RMSE value was selected. Independent control of 3D model accuracy was based on seven heap control points measured in the field and the same points generated on the 3D model . The deviations of several centimeters between field control points and points from the model may indicate the great potential of UAV technology and the possibility of its use in various engineering tasks.